Microfacies of the Tulian Horizon (Visean Stage, Lower Carboniferous) of the Sikaza 2 section (Southern Urals, Russia) - E.N. Gorozhanina; E.Yu. Bashlykova; E.I. Kulagina (Учёные записки Казанского университета: Серия Естественные науки)
The Carboniferous deposits of the Sikasi (Sikaze) River sections in the western part of the Southern Urals are of great geological importance and included in the list of particularly significant sites of the Toratau Geopark of the Republic of Bashkortostan. In this article, a lithofacies description of the carbonate deposits of the Tulian Horizon of the Visean Stage in the Sikaza 2 section near the Sikasi River was performed based on the microfacies analysis of carbonate rock sections of the samples from the collection of the Museum of Geology and Mineral Resources of the Republic of Bashkortostan (Ufa, Russia). Micro-description of limestones was carried out with the help of R. Dunham’s classification, E. Flügel’s methodology. The revealed textural and structural features and the composition of faunal remains in the Tulian deposits of the Sikaza 2 section allowed us to identify and describe in detail five microfacies of limestones that developed under the open-shelf conditions. The sequence of these microfacies indicates the alternation of sediments of currents and waves in the early Tulian time, which was followed by the gradual shallowing and formation of the shallow-shelf conditions by its end.